Standardization of Epidemiological Surveillance of Group A Streptococcal Impetigo . (15th September 2022) - Miller, Kate M; Carapetis, Jonathan R; Cherian, Thomas; Hay, Roderick; Marks, Michael; Pickering, Janessa; Cannon, Jeffrey W; Lamagni, Theresa; Romani, Lucia; Moore, Hannah C; Van Beneden, Chris A; Barth, Dylan D; et al.
Abstract: Impetigo is a highly contagious bacterial infection of the superficial layer of skin. Impetigo is caused by group A Streptococcus (Strep A) and Staphylococcus aureus, alone or in combination, with the former predominating in many tropical climates. Strep A impetigo occurs mainly in early childhood, and the burden varies worldwide. It is an acute, self-limited disease, but many children experience frequent recurrences that make it a chronic illness in some endemic settings. We present a standardized surveillance protocol including case definitions for impetigo including both active (purulent, crusted) and resolving (flat, dry) phases and discuss the current tests used to detect Strep A among persons with impetigo. Case classifications that can be applied are detailed, including differentiating between incident (new) and prevalent (existing) cases of Strep A impetigo. The type of surveillance methodology depends on the burden of impetigo in the community. Active surveillance and laboratory confirmation is the preferred method for case detection, particularly in endemic settings. Participant eligibility, surveillance population and additional considerations for surveillance of impetigo, including examination of lesions, use of photographs to document lesions, and staff training requirements (including cultural awareness), are addressed. Finally, the core elements of case report forms for impetigo are presented and guidance for recording the course and severity of impetigo provided.